Problematic cryptoasset trading is associated with greater depressive symptoms, anxiety symptoms, and social isolation - Dar Meshi; Dayeoun Jang; Zijie Mei; Rabindra Ratan; Maxwell Foxman (PLoS ONE, 2026)
Public blockchains allow individuals to own, trade, and transfer digital cryptoassets on the internet. These cryptoassets are highly volatile and available to trade 24 hours a day, seven days a week. The potential financial rewards stemming from buying and selling cryptoassets create the possibility for individuals to display a maladaptive behavior, problematic cryptoasset trading, which can be considered as a type of problematic gambling. Prior research has demonstrated that behavioral addictive disorders, like gambling disorder, are associated with poor mental health. In addition, previous research has revealed that individuals who simply trade cryptoassets describe experiencing more negative mental health symptoms in comparison to non-investing individuals. Therefore, we hypothesized that problematic cryptoasset trading would be positively associated with three measures of mental health: depressive symptoms, anxiety symptoms, and social isolation. We collected cross-sectional survey data (N = 239; female = 78, male = 161) and ran hierarchical linear regressions, controlling for demographic characteristics. Our analyses supported the hypothesized associations between problematic cryptoasset trading and the three mental health measures. In other words, higher levels of problematic cryptoasset trading were associated with higher levels of depressive symptoms, anxiety symptoms, and social isolation. Implications for further research and clinical practice are discussed.